Efn1 and Efn2 are extracellular 5'-nucleotidases induced during the fission yeast response to phosphate starvation - Aleksei Innokentev; Ana M. Sanchez; Mara Monetti; Beate Schwer; Stewart Shuman (mBio)
ABSTRACT The fission yeast PHO regulon genes pho1, pho84, and tgp1—encoding a cell surface-associated acid phosphatase (Pho1), a plasma membrane inorganic phosphate transporter (Pho84), and a plasma membrane glycerophosphocholine transporter (Tgp1)—are strongly upregulated in response to acute phosphate starvation, as are the SPBPB2B2.06c and SPAC1039.02 genes that encode putative 5'-nucleotidase paralogs of the binuclear metallophosphoesterase enzyme superfamily. Via proteomic analysis of the medium harvested from phosphate-replete and phosphate-starved fission yeast, we define a starvation secretome that includes SPBPB2B2.06c (renamed Efn1, for extracellular five-prime nucleotidase), SPAC1039.02 (henceforth Efn2), and Pho1 among the most abundant exported proteins elaborated by phosphate-starved cells. We demonstrate and characterize a 5'-nucleotidase activity secreted into the medium of phosphate-starved efn1+efn2+ cells, which is eliminated by simultaneous deletion of efn1 and efn2. By singly deleting efn1 and efn2, we find that Efn1 contributes the greater share of secreted 5'-nucleotidase activity. Efn1 and Efn2 catalyze the release of inorganic phosphate from all four standard ribonucleoside monophosphates, in order of preference: CMP > UMP > AMP > GMP. Whereas efn1+efn2+ cells can use extracellular CMP as a source of phosphate during phosphate starvation, efn1∆ efn2∆ cells cannot. The secretion of 5'-nucleotidase enzymes during phosphate limitation is a newly appreciated facet of fission yeast phosphate homeostasis.IMPORTANCESchizosaccharomyces pombe adapts to phosphate starvation by upregulating the expression of a cell surface acid phosphatase that mobilizes inorganic phosphate from the extracellular milieu, as well as transmembrane transporters that take up inorganic phosphate and glycerophosphocholine. This study identifies two paralogous extracellular 5'-nucleotidase enzymes, Efn1 and Efn2, encoded by genes that are highly transcriptionally induced during acute phosphate starvation, as major proteins secreted into the medium by phosphate-starved fission yeast cells. Secreted Efn1 and Efn2 catalyze the release of inorganic phosphate from all ribonucleoside monophosphates, with a preference for CMP. Secretion of Efn1 and Efn2 enables phosphate-starved fission yeast to thrive by using extracellular CMP as a source of inorganic phosphate. The starvation-induced production of extracellular 5'-nucleotidases adds a new layer of pro-adaptive function during phosphate limitation.